Optimalisasi Wewenang Dan Tanggung Jawab Hakim Pengawas Dalam Hukum Kepailitan Di Indonesia - Aprita, Serlika; Qosim, Sarah (Magister Hukum Universitas Semarang, 2022)
This article aims to analyze the legal certainty of Law No. 37 of 2004 on Bankruptcy and PKPU related to the implementation of the duties, authorities, and responsibilities of bankruptcy supervisory judges in supervising the management and execution of bankruptcy property in the Surabaya Commercial Court. The research method used in this article is empirical juridical with case approach. The writing of this article first reviewed previous research related to the role and authority of supervisory judges in the Commercial Court, but in each article only describes the contents of the provisions of Law No. 37 of 2004 on Bankruptcy and PKPU related to the role and authority of bankruptcy law supervisory judges, and then this article analyzes the legal certainty of the enforcement of the authority and responsibility of the supervisory judge in the Surabaya Commercial Court on charges of having received bribes from PT Sky Camping Indonesia (SCI) as a curator in the bankruptcy process. The results of this article show that the legal certainty of Law No. 37 of 2004 on Insolvency and PKPU related to the authority and responsibility of supervisory judges, in practice in the field is not fully operational. The supervisory judge does not carry out his duties and authority to oversee the management and release of bankruptcy property because it has received bribes from PT SCI as a curator so that the supervisory judge determines the verdict of the debtor's bankruptcy assets to non-bankruptcy.Artikel ini bertujuan untuk menganalisa kepastian hukum Undang-Undang No. 37 tahun 2004 tentang Kepailitan dan PKPU terkait pelaksanaan tugas, kewenangan, dan tanggung jawab Hakim Pengawas kepailitan dalam mengawasi pengurusan dan pemberesan harta pailit di Pengadilan Niaga Surabaya. Metode penelitian yang digunakan dalam artikel ini adalah yuridis empiris dengan pendekatan kasus (case approach). Penelitian artikel ini terlebih dahulu mereview penelitian-penelitian sebelumnya terkait peran dan wewenang Hakim Pengawas di Pengadilan Niaga, namun pada masing-masing artikel tersebut hanya memaparkan isi ketentuan Undang-Undang No. 37 tahun 2004 tentang Kepailitan dan PKPU terkait peran dan wewenang Hakim Pengawas hukum kepailitan, selanjutnya artikel ini menganalisa kepastian hukum pelaksaan Undang-Undang No. 37 tahun 2004 tentang Kepailitan dan PKPU terkait wewenang dan tanggung jawab Hakim Pengawas di Pengadilan Niaga Surabaya atas dakwaan telah menerima suap dari PT Sky Camping Indonesia (SCI) sebagai Kurator dalam proses kepailitan. Hasil artikel ini menunjukkan bahwa kepastian hukum Undang-Undang No. 37 tahun 2004 tentang Kepailitan dan PKPU terkait wewenang dan tanggung jawab Hakim Pengawas, dalam praktiknya di lapangan tidak sepenuhnya berjalan. Hakim Pengawas menyalahgunakan tugas dan wewenangnya untuk mengawasi pengurusan dan pemberesan harta pailit dikarenakan telah menerima suap dari PT SCI sebagai Kurator supaya Hakim Pengawas menetapkan putusan aset pailit debitur menjadi non pailit.